Association of Deviated Nasal Septum with Chronic Otitis Media in Western Regional Hospital - Goudel, Bonu; Sharma, Swasti; Bhandari, Akash Mani; Shakya, Ambalika; Chapagain, Anup; Gurung, Lal Bdr (Journal of Bharatpur Hospital, 2026)
Background Chronic otitis media (COM) is a persistent inflammation of the middle ear and mastoid cavity characterized by recurrent otorrhea through a perforated tympanic membrane and/or tympanic membrane retraction. Eustachian tube dysfunction (ETD), often resulting from chronic nasal disease, has been implicated in the pathogenesis of COM. Deviated nasal septum (DNS), one of the most common nasal abnormalities, may contribute to ETD by altering middle ear pressure. However, this association remains underrecognized in clinical practice due to inadequate evaluation. This study aimed to assess the association between DNS and COM. Methods A hospital-based cross-sectional study was conducted among 122 patients diagnosed with COM who attended the ENT outpatient department of Pokhara Academy of Health Sciences from June 2025 to May 2026. Diagnosis was established by trained ENT surgeons based on clinical history and otoscopic findings, including tympanic membrane perforation, cholesteatoma, and/or retraction pocket. Patients meeting the inclusion and exclusion criteria underwent anterior rhinoscopy, with local decongestant when required, to assess the presence, side, and type of DNS. Data were analysed to determine the association between COM and DNS. Results Among the 122 patients, 102 (83.6%) had DNS. Statistical analysis demonstrated a significant association between COM and DNS. Conclusions A significant association was observed between COM and DNS, suggesting that DNS may contribute to the persistence of COM through Eustachian tube dysfunction. Routine evaluation and appropriate management of DNS before ear surgery may improve treatment outcomes in patients with chronic otitis media.